2018
DOI: 10.1016/j.apsusc.2017.12.197
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline CeO2−δ coated β-MnO2 nanorods with enhanced oxygen transfer property

Abstract: In this research, β-MnO 2 nanorods were synthesized by a hydrothermal method, followed by a facile precipitation method to obtain nanocrystalline CeO 2-δ coated β-MnO 2 nanorods. The as-prepared samples were characterized by XRD, HRTEM, FESEM, XPS and in-situ high-temperature XRD. The HRTEM results show that well dispersed CeO 2-δ nanocrystals sized about 5 nm were coated on the surface of β-MnO 2 nanorods. The oxygen storage and transfer property of as-synthesized materials were evaluated using TGA under vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The O 1s spectrum included two individual peaks located at 529.80 and 531.50 eV in DC polarization deposit (Figure b) and 529.60 and 531.30 eV in PC-500 Hz polarization deposit (Figure e). These were ascribed to the surface lattice oxygen of metal oxides (O 2– ) and adsorbed oxygen or surface hydroxyl species, respectively. , The asymmetric Mn 2p 3/2 main peak was found at 642.0 eV with a 2p 3/2 to 2p 1/2 peak at 653.7 eV splitting of 11.7 eV. This was in good agreement with the energy splitting of the standard spectrum of MnO 2 . , As shown in Figure c, the main peaks at 641.57 and 640.40 eV of Mn 2p 3/2 wer ascribed to Mn­(III) and peaks at 643.4, 645.0, and 646.0 eV were attributed to Mn­(IV), , The results indicated that the oxidation state of Mn in deposited MnO 2 was mainly Mn­(III) but with some Mn­(IV) after DC polarization.…”
Section: Resultssupporting
confidence: 80%
“…The O 1s spectrum included two individual peaks located at 529.80 and 531.50 eV in DC polarization deposit (Figure b) and 529.60 and 531.30 eV in PC-500 Hz polarization deposit (Figure e). These were ascribed to the surface lattice oxygen of metal oxides (O 2– ) and adsorbed oxygen or surface hydroxyl species, respectively. , The asymmetric Mn 2p 3/2 main peak was found at 642.0 eV with a 2p 3/2 to 2p 1/2 peak at 653.7 eV splitting of 11.7 eV. This was in good agreement with the energy splitting of the standard spectrum of MnO 2 . , As shown in Figure c, the main peaks at 641.57 and 640.40 eV of Mn 2p 3/2 wer ascribed to Mn­(III) and peaks at 643.4, 645.0, and 646.0 eV were attributed to Mn­(IV), , The results indicated that the oxidation state of Mn in deposited MnO 2 was mainly Mn­(III) but with some Mn­(IV) after DC polarization.…”
Section: Resultssupporting
confidence: 80%
“…Nevertheless, there are more CeO 2−δ nanocrystals observed in Ce-MnCo 2 O 4 -7%, as illustrated in its HRTEM (Figure h) and STEM EDS elemental mapping images (Figure i). The coprecipitated method is facile to uniformly distribute Ce species into hierarchically nanostructured MnCo 2 O 4 , which may not only enhance the oxygen and electron transfer between Ce species and MnCo 2 O 4 to improve the electrochemical performance but also keep catalyst stable during the electrocatalytic reactions …”
Section: Resultsmentioning
confidence: 99%
“…The prepared samples were named as Ce-MnCo 2 O 4 - x , in which x is the molar ratio (1%, 3% or 7%) of Ce­(NO 3 ) 3 ·6H 2 O to MnCo 2 O 4 . Pure CeO 2−δ nanowires were obtained according to our previous work …”
Section: Methodsmentioning
confidence: 99%
“…Figure 2(c) shows the high-resolution XPS spectra of Ce 3d peaks of the CeO 2 /MnO 2 -CFP sample. The three peaks centered at ~882.5, ~888.8, and ~898.4 eV could be assigned to Ce 4+ 3d 5/2 , the three peaks centered at ~901.1, ~907.3, and ~916.7 eV could be assigned to Ce 4+ 3d 3/2 , and another two peaks located at ~885.6 and ~903.3 eV corresponded to Ce 3+ 3d 5/2 and Ce 3+ 3d 3/2 , respectively [51][52][53]. The Ce 3+ /Ce 4+ ratio was determined at 0.13, and the coexistence of Ce 4+ and Ce 3+ could be attributed to the use of Ce(NO 3 ) 3 •6H 2 O as the Ce source during the synthesis process.…”
Section: Chemical Composition Of the Ceo 2 /Mno 2 -Cfp Samplementioning
confidence: 98%